Development of Mathematics Assessment Instruments for High School Students Based on Higher-Order Thinking Skills (HOTS) - Ellis Mardiana Panggabean; Feri Haryati; Sri Wahyuni (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to develop a mathematical assessment instrument for senior high school students based on higher order thinking skills (HOTS). This research is development research that aims to develop a valid, practical and effective HOTS assessment instrument. The development model used is the Tessmer’s model. There are five steps applied in this study, namely preliminary, self-evaluation, expert review, one-to-one and small group and field testing.  The research findings explained that each item met the validity of content (content), construct, and language. Content validity is the compatibility between the questions and the indicators that have been set for each material. Fulfilling construct validity refers to the instrument measured by the HOTS concept. It met the validity of the language because the sentence structure in the question followed the correct Indonesian language rules and did not contain double meanings or ambiguity. Therefore, this item is appropriate to be used as an alternative teaching material for students to develop their higher-order thinking skills, especially in the material about flat-plane analytical geometry.